Nilai Karakter dalam Puisi Karya Thayeb Loh Angen - Marzatillah, Wini; Maulidia, Maulidia; Dwita, Syarafina; Ula, Shahiratul; Syakila, Dara (Medan Resource Center, 2024)
The poetry of Thayeb Loh Angen, a prominent Acehnese poet, embodies profound personal and cultural values that resonate deeply with the lived experiences of society. This study aims to identify and critically analyze the character values embedded in his poetic works. The central research question addresses how these values are articulated through literary devices and thematic structures within his poetry. Employing a qualitative descriptive approach, this research utilizes content analysis to examine the dominant themes and moral messages conveyed. The findings reveal that core character values—such as religiosity, wisdom, patriotism, environmental awareness, justice, and humanity—are consistently reflected across his body of work. These values are conveyed through symbolic language, metaphor, and a lyrical style rooted in Acehnese tradition, evoking emotional depth and moral reflection in readers. The study concludes that Thayeb Loh Angen’s poetry serves not only as an artistic expression but also as an effective medium for character education, offering meaningful insights into ethical behavior, social responsibility, and cultural identity, particularly within the Acehnese context.